Penerapan Strategi Reading Aloud Di Kelas V SDN 02 Sasak Ranah Pasisie - Mai Sri Lena; Hana Shilfia Iraqi; Nulfa Aidina; Tuti Erawati (Universitas Palangka Raya, 2023)
This study discusses the strategy of reading aloud in fostering students' desire to read in Class V SDN 02 Sasak Ranah Pasisie. Because reading is one of the language skills needed in activities or doing routines, especially in learning at school. The purpose of this research is to explain what factors affect students' reading interest in class V SDN 02 Sasak Ranah Pasisie and to explain the application of a screen reading strategy by the teacher in increasing students' reading interest in class V SDN 02 Sasak Ranah Pasisie. The method used in this research is qualitative, with a descriptive approach, where the researcher describes the results of his research precisely and in accordance with the results obtained during the survey. From the survey conducted through interviews, teachers and distributing questionnaires to students, it shows that students' interest in reading is influenced by several factors, such as: (I) external factors such as guidance from parents, media for reading and from educators (2) factors or influences from within such as self-influences. With the strategy of reading aloud the teacher of grade V was effective, the students seemed eager to read and some even took the initiative to read.